2020
DOI: 10.3390/agronomy10091426
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Induces Differentiated Nitrogen Uptake and Antioxidant Responses in Two Contrasting Barley Landraces from MENA Region

Abstract: The interaction between salinity and nitrogen metabolism has been investigated in two barley landraces, one tolerant (“100/1B”) and one susceptible to salinity (“Barley medenine”) from the Middle East and North Africa (MENA) region. Barley plants were exposed to 50 mM NaCl for 7 days; then, salinity was increased to 150 mM NaCl in the presence (10 mM) or limitation (1 mM) of ammonium as a nitrogen source. Upon salinity, “100/1B” was shown to support N assimilation by enhancing the glutamine synthetase (GS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, rare information is available about the role of minerals and their dynamics in salt-tolerant plants [21]. Potassium and silicon are elements with positive effects on the plant performance under saline stress [22][23][24][25][26]. Several studies report that both elements are significantly able to improve plant growth and crop productivity, enhance the photosynthesis rate and water use efficiency, and increase the antioxidant enzymatic activity and plant tolerance to diseases, under adverse environmental conditions [5,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, rare information is available about the role of minerals and their dynamics in salt-tolerant plants [21]. Potassium and silicon are elements with positive effects on the plant performance under saline stress [22][23][24][25][26]. Several studies report that both elements are significantly able to improve plant growth and crop productivity, enhance the photosynthesis rate and water use efficiency, and increase the antioxidant enzymatic activity and plant tolerance to diseases, under adverse environmental conditions [5,27].…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that NaCl stress decreased N assimilation by damaging the enzymes related to N metabolism, which could be one of the main reasons for the growth reduction induced under NaCl stress. The results of the disturbance in N metabolism under NaCl toxicity have already been supported by Ben Azaiez et al [ 47 ]. Shao et al [ 48 ] showed that salt stress downregulated the expression levels of NR , GS , and GOGAT enzymes and, as a result, diminished N metabolism.…”
Section: Discussionmentioning
confidence: 60%
“…Among major crops, barley is the fourth most cultivated cereal, representing one of the main sources of carbohydrates in developing countries (FAOstat 2019-9), where it represents one of the main resources grown by small farmers in many arid areas [6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%